Patient Care Monitoring and Mobile Notification Using Health Care IoT - Dhasarathi, M; Priyadharshini, R (International Journal of Computer Sciences and Engineering, 2025)
The Internet of Medical Things (IoMT) is the collection of medical devices and applications that connect to healthcare IT systems through online computer networks. Medical devices equipped with Wi-Fi allow the machine to machine communication that is the basis of IoMT. IoMT devices link to cloud platforms such as Amazon Web Services, on which captured data can be stored and analyzed. IoMT is also known as healthcare IoT. The proposed idea is based on the advancement of new advanced technology and Internet of Things which act as an airing device for patient care identification and patient care monitoring. It allows doctors to attend manifold of patients in rural areas without regular concentrating on a single patient. It also includes mobile notifications to doctors if the patient condition is critical. The (IoMT) is an incorporation of medical devices and applications that can connect to healthcare ideas using networking technologies. It connects patients to their doctors and allows transfer of medical data over a secure network, which in turn reduces unnecessary hospital visits and reduces the burden on healthcare ideas largely. In this paper an IoT idea will be developed to monitor the patient with this chronic disorder using cloud data logging. The developed idea can also be used to monitor various other parameters of patients such as Respiration, Body temperature, Pressure and the same can be logged every 20 seconds on cloud services. The doctors can monitor the patient’s data using his mobile phone by logging into the cloud service and take necessary actions according to the parameters measured